A scoping/mapping literature review about Urban and Periurban Agriculture (UPA) - Sellin, Victor Bueno; Christopoulos, Tania Pereira (Revista de Administração da UFSM, 2020)
The world is undergoing an accelerated urbanization process marked by social and environmental imbalances. In this context, urban and periurban agriculture (UPA) emerges as an alternative to sustainable urbanization mainly due to its contribution to food security, reduction of environmental impact, revitalization of urban areas, integration of households and physical and psychological well-being increasing. The purpose of this paper is to understand how academic literature deals with urban and periurban agriculture. For that, a scoping / mapping literature review was carried out and its results were presented after identification of relevant scientific studies on UPA, its main aspects, ways in which the term has been defined; and discussion about themes from the selected articles. After this review, the conclusions are: the scientific production on the subject is undergoing high growth rates in recent years; the relationship between UPA and urban dynamics is more important for the definition of UPA than the location of agriculture; and that the aspects that authors found most interesting are: concept and panorama, urban planning and governance, quantitative potential, environment, risk of contamination and techniques and productivity.